The mortality and cancer experience of New Zealand Vietnam war veterans: a cohort study. Issue 9 (2nd September 2013) - McBride, David; Cox, Brian; Broughton, John; Tong, Darryl
Abstract : Objectives: The aim was to observe the patterns of mortality and cancer incidence in New Zealand Vietnam veterans. The objectives were to assess whether the patterns of disease observed were consistent with those associated with military service in Vietnam, and similar to the patterns identified in other groups of Vietnam veterans. Design: A historical cohort study. Setting: Veterans, identified from service records, with Vietnam service between 1964 and 1972. Participants: Of the 3322 survivors of Vietnam service, we followed up 2783 (84%). Outcome measures: Standardised mortality and incidence ratios (SMRs and SIRs, respectively) were calculated based on the number of deaths and cancer registrations observed, those expected being based on New Zealand national rates. Results: All cause mortality was significantly reduced (SMR 0.85, 95% CI 0.77 to 0.94) and cancer incidence non-significantly increased (SIR 1.06, 95% CI 0.97 to 1.16). The risk of mortality from cancers of the head and neck (SMR 2.20, 95% CI 1.09 to 3.93); oral cavity pharynx and larynx (SMR 2.13, 95% CI 1.06 to 3.81) and the incidence of chronic lymphatic leukaemia (CLL) (SIR 1.91, 95% CI 1.04 to 3.20) were, however, significantly increased. Other lymphohaematopoietic disorders, specifically multiple myeloma and Hodgkin disease, showed non-significant mortality excesses, reflected by a similar increase in incidence. Conclusions: Service in the Vietnam war was associated with defoliant herbicide exposure, including 2, 4, 5-trichlorophenoxyacetic acid, 2, 4-dichlorophenoxyacetic acid, picloram and cacodylic acid. Subsequent reviews of mechanistic, animal and epidemiological evidence led to certain conditions being deemed compensable. The pattern of mortality and cancer incidence is not at odds with the list of compensable conditions and consistent with that found in Australian veterans serving in the same area of Vietnam, but also consistent with smoking and the healthy soldier effect. In common with the Australian experience, this is the only veterans group to show a significant excess of CLL.